University students' meal experience at the dining hall: meal experience - Unusan, Nurhan (Progress in Nutrition, 2020)
Objective: The objectives of the study were If BMI is a statistically significant predictor of detailednutrition facts on menu labels, and to compare and describe the level of satisfaction of the university students’meal experience on meals, preparation, value, service and ambience both in 2016 and 2017. Material and Method: The study was carried out in a fully operational dining hall where students book, dine and pay for meals at ba foundation University in Konya, Turkey. Both in 2016 and 2017 the level of satisfaction of the University students’ meal experience was measured. In 2017, both BMI and nutrition facts measurements were included and the author and 4 other people from the same university was in charge of monthly audit on hygiene, sanitation and nutrition labelling in the dining hall between the application of questionnaires. A self-report questionnaire was developed. The questionnaire consists of two main sections; level of satisfaction on meal experience, calorie and macronutrient level information on restaurant menus. The variables were investigated using Kolmogorov-Smirnov to determine if they are normally distributed. To compare the mean of two groups, gender and years Mann-Whitney U test was used. To compare BMI classifications Kruskal-Wallistest was preferred. Furthermore, the Chi-square test was used to compare the proportions of variables in crosstabulation. Results: There is a statistically significant difference when cross-tabulation of macronutrients andtotal calories with BMI are examined (=21,842; p=0,0390,05). Conclusions: This study determined the level of satisfaction that students have with their meal experiences in order to improve the food service provided. The methods can be transferrable to other dining settings, such as schools, hospitals and even workplaces.